(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
About the Modification of the Choice to Attend or not Attend Teaching of Catholic Religion. A School Point of View ABSTRACT: A recent judgement of the Judicial Administration has authorized the free modification of the choice to attend or not attend teaching of Catholic Religion in Italian schools, against the Concordat between Italian Republic and Holy See. The article discusses the judgement formally (highlighting a lack of jurisdiction) and on the substance (a confusion between a cultural and a cultic meaning of the teaching). In addition to institutional relations between State and Church, there are epistemological consequences on the nature of the same teaching. SOMMARIO: 1. Attualità del problema - 2. La normativa sulle iscrizioni e la scelta di avvalersi o non avvalersi dell’insegnamento della religione cattolica (Irc) - 3. Il caso in giudizio - 4. Sul difetto di giurisdizione - 5. Le motivazioni della sentenza: il richiamo alla libertà di culto - 6. Un Irc culturale o cultuale? - 7. Un bilanciamento poco equilibrato - 8. L’Irc come disciplina scolastica - 9. In attesa di revisioni.